Study and remediation of trade effluent in shipyards - Lee, Jonathan Tze Siong. (2010)
Shipyards generate trade effluent through activities including chemical washing, non-destructive testing and maintenance. The resulting discharge may contain numerous hazardous contaminants. In order to consistently meet stringent regulatory requirements a reliable and cost effective treatment system is essential. This report investigates the wastewater stream from the maintenance workshop within a local shipyard and determines that a ferric chloride dosage as low as 25.0 mg/L is capable of both coagulating and flocculating the effluent effectively. Pre-coagulation pH adjustment presented marginal benefits but is eschewed in favour of supporting a more comprehensive solution. The overall removal efficiency of soluble COD through pre-treatment, microfiltration and ozonation was as high as 82.5% and resulted in effluent COD of only 11.0 mg/L. TSS was reduced to less than 1 mg/L pre-filtration. The colour factor was reduced from 13 to 3 units. Turbidity was reduced to below 1 NTU and TDS was reduced 44.3% to 146.7 mg/L. A suitable treatment schematic was developed to ensure compliance with the local sewage regulations outlined in the COPPC. The cost considerations in the design process eliminate unnecessary expenditure for the shipyard. The low effluent flow rate of 15 m3/day inspired a novel design for the clarification stage. The treatment system will incorporate rapid and slow mix stages, clarification, microfiltration and reverse osmosis as well as a compact sludge dewatering system. Automation of the system enables off-peak hours energy cost reductions of up to 40%. The quality of the treated water will satisfy the requirements for recycle within the shipyard. Operating costs are offset by the reduction in PUB water tariffs through the water reclamation and recycle process. However the majority of the associated costs are capital in nature. A full return on investment spans over more than a decade due to the high capital costs and low daily volume of water treatment. Depending on the configuration of the treatment system the net cash flow for the amortized project can be either positive or negative. However at less than $500 per month this does not represent a substantial amount in light of factors such as reduced legal exposure, enhanced corporate image and environmental benefits.